2014
DOI: 10.3390/math2010012
|View full text |Cite
|
Sign up to set email alerts
|

On the Folded Normal Distribution

Abstract: The characteristic function of the folded normal distribution and its moment function are derived. The entropy of the folded normal distribution and the Kullback-Leibler from the normal and half normal distributions are approximated using Taylor series. The accuracy of the results are also assessed using different criteria. The maximum likelihood estimates and confidence intervals for the parameters are obtained using the asymptotic theory and bootstrap method. The coverage of the confidence intervals is also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 18 publications
3
43
0
1
Order By: Relevance
“…This validates the observation made by Tsagris et al [16] that, for the said BMI data, the fitted folded normal converges in distribution to normal distribution.…”
Section: Example 2 (Based On Leone Et Al's [1] Data)supporting
confidence: 91%
See 1 more Smart Citation
“…This validates the observation made by Tsagris et al [16] that, for the said BMI data, the fitted folded normal converges in distribution to normal distribution.…”
Section: Example 2 (Based On Leone Et Al's [1] Data)supporting
confidence: 91%
“…Tsagris et al [16] have shown that the data on BMI follow folded normal distribution. Thus, from the said data, we haveμ f = 26.6847 andσ f = 4.6213.…”
Section: Example 2 (Based On Leone Et Al's [1] Data)mentioning
confidence: 96%
“…the half-normal distribution). Thus, the expectation value is precisely the imaginary part of the folded-normal characteristic function [64]:…”
Section: Second Order Term Of the Magnus Expansionmentioning
confidence: 99%
“…Let W=|Y|, then FW(w)=Nf(μ,σ2), where Nf means a folded normal distribution. Its probability density function isleftf(w)=1σ[φ(wμσ)+φ(w+μσ)]=1σ2π{exp(12(w+μσ)2)+exp(12(wμσ)2)},     w[0,).The expectation of W isE(W)=μ[12Φ(μ/σ)]+σ2πexp(μ2/2σ2).Details of folded normal distribution can be found in Tsagris et al (2014). Now, we will proceed to evaluate CRPS(FYo,μS)=EF|YoμS|12EF|YoYo| as follows.…”
Section: Univariate Kullback-leibler Loss Derivationmentioning
confidence: 99%